La metacomunicación como dispositivo central de la intervención organizacional: enfoque comunicacional de la escuela de Lovaina (2004)
In this article we will develop the communicational approach of the Louvain’s school, which is centred in the analysis of the tool in the intervention and induction of the change in the organisations. We will approach the description of the system of the intervention, the analysis of the leveis of the pilotage in itself –current pilotage and metapilotage– and the indicators of the metapilotage, in which the built metacommunication is the central axis of the comptroller–consultant work